Prevalent components of metabolic syndrome and their correlates in apparently healthy individuals in Sub-Saharan Africa (2014)
Aim: To assess the prevalent components of metabolic syndrome (MSC) and their related determinants of lipid metabolism in the Nigerian for early diagnosis, prevention and management of the metabolic syndrome (MS) and its associated diseases. Study Design: Cohort study. Place and Duration of Study: Department of Chemical Pathology, College of Medicine, University of Ibadan, Ibadan between March and August 2010. Methodology: 534 apparently healthy Nigerian traders aged 18–105 years were participants of a cohort study. The IDF (2005) criteria was used for MS diagnosis. Anthropometric indices and blood pressure (BP) were obtained by standard methods. Fasting plasma glucose, total cholesterol (TC), triglycerides (TG) and high density lipoprotein cholesterol (HDLC) were determined by enzymatic methods while low density lipoprotein cholesterol (LDLC) was calculated. Data analysed were statistically significant at P<0.05. Results: 60.1% of traders had 2 and 3MSC. 0.6%, 1.1% and 9.6% of traders had all 5MSC, ≥3MSC without elevated waist circumference (WC) and zero MSC respectively. Elevated WC, reduced HDLC and high BP were more frequent MSC representing 70.2%, 63.1% and 47.9% while FPG and TG were less frequent representing 11.2% and 2.2% of traders respectively. This pattern was similar in MS and non-MS groups. 25.3% of males and only 2.2% of females had no MSC. Reduced HDLC and elevated WC were the most frequent MSC in males and females respectively. All metabolic risk factors (MRF) except TC were significantly different in comparison between MS and non-MS groups as well as among traders with 0-5 MSC. WHR was the only parameter that correlated significantly with all MRF. Conclusion: Elevated waist circumference, reduced high density lipoprotein cholesterol, and high blood pressure may be prevalent metabolic syndrome components and important in managing metabolic syndrome in Nigeria. Regional specific cut-offs for these components for the African population is needed.